Managing Biofouling on Submerged Static Artificial Structures in the Marine Environment – Assessment of Current and Emerging Approaches - Hopkins, Grant; Davidson, Ian; Georgiades, Eugene; Floerl, Oliver; Morrisey, Donald; Cahill, Patrick (Frontiers in Marine Science, 2021)
The number, extent, diversity, and global reach of submerged static artificial structures (SSAS) in the marine environment is increasing. These structures are prone to the accumulation of biofouling that can result in unwanted impacts, both immediate and long-term. Therefore, management of biofouling on SSAS has a range of potential benefits that can improve structure functions, cost-efficiency, sustainability, productivity, and biosecurity. This review and synthesis collates the range of methods and tools that exist or are emerging for managing SSAS biofouling for a variety of sectors, highlighting key criteria and knowledge gaps that affect development, and uptake to improve operational and environmental outcomes. The most common methods to manage biofouling on SSAS are mechanical and are applied reactively to manage biofouling assemblages after they have developed to substantial levels. Effective application of reactive methods is logistically challenging, occurs after impacts have accumulated, can pose health and safety risks, and is costly at large scales. Emerging technologies aim to shift this paradigm to a more proactive and preventive management approach, but uncertainty remains regarding their long-term efficacy, feasibility, and environmental effects at operational scales. Key priorities to promote more widespread biofouling management of SSAS include rigorous and transparent independent testing of emerging treatment systems, with more holistic cost-benefit analyses where efficacy is demonstrated.